Host-guest supramolecular hydrogel based on nanoparticles: co-delivery of DOX and siBcl-2 for synergistic cancer therapy. Issue 10 (3rd July 2019) - Peng, Dan; Gao, Huijie; Huang, Pingsheng; Shi, Xiaoguang; Zhou, Junhui; Zhang, Jianhua; Dong, Anjie; Tang, Hua; Wang, Weiwei; Deng, Liandong
Abstract: Synergistic therapy that combines drug/siRNA for the solid tumor treatment is becoming more and more popular to reduce the side effects and enhance the antitumor efficiency. Given that, a novel injectable supramolecular hydrogel mPECT(D)/GDDC-4(R)/α-CD gel (mPECT(D) represents DOX-loaded methoxy poly(ethylene glycol)-b-poly(ε-caprolactone-co-1, 4, 8-trioxa[4.6]spiro-9-un-decanone) (mPECT) nanoparticles, GDDC-4(R) represents siBcl-2-loaded PG-P(DPAx-co-DMAEMAy)-PCB (GDDC-4) complexes nanoparticles (NPs)) was prepared via the incorporation of GDDC-4/siRNA complexes NPs into the DOX-loaded mPECT NPs/α-CD gel formed by the host-guest interaction between mPEG and α-CD. In vitro degradation and release experiments revealed that siBcl-2 was released from mPECT(D)/GDDC-4(R)/α-CD gel in the form of GDDC-4/siBcl-2 complexes NPs with bioactivity, and the release behavior of DOX also demonstrated sustained-release property. Compared to the single treatment groups, the enhanced cytotoxicity to SKOV3 and HeLa cells of mPECT(D)/GDDC-4(R)/α-CD gel was observed in vitro . Moreover, in vivo experiments also indicated the significant antitumor effect of mPECT(D)/GDDC-4(R)/α-CD gel, suggesting the remarkable synergistic therapy of DOX and siBcl-2. Therefore, this work would provide a prospective platform to co-delivery of drugs and siRNA to improve the treatment effect of solid tumor.